2018
DOI: 10.1096/fj.201701543rr
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II increases angiogenesis by NF‐κB–mediated transcriptional activation of angiogenic factor AGGF1

Abstract: Angiogenic factor with G-patch and FHA domains 1 (AGGF1) is involved in vascular development, angiogenesis, specification of hemangioblasts, and differentiation of veins. When mutated, however, it causes Klippel-Trenaunay syndrome, a vascular disorder. In this study, we show that angiotensin II (AngII)-the major effector of the renin-angiotensin system and one of the most important regulators of the cardiovascular system-induces the expression of AGGF1 through NF-κB, and that AGGF1 plays a key role in AngII-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…24 In addition, the synthesis of NF-κB can be promoted by angiotensin II, which is a transcriptional factor that up-regulates the expression of adherence factors, inflammatory factors, epoxidase-2, and angiotensinogen. 25,26 It is reported that Angiotensin II-induced mitochondrial dysfunction reduces endothelial NO bioavailability and promotes ROS generation, 27 therefore Angiotensin II-impaired mitochondrial function could be one of the mechanisms of endothelial dysfunction. Besides, the renin-angiotensin system (RAS) can be activated by angiotensin II to inhibit the function of progenitor cells, which has been reported to be beneficial to the recovery of VEC function and alleviates the symptoms of arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, the synthesis of NF-κB can be promoted by angiotensin II, which is a transcriptional factor that up-regulates the expression of adherence factors, inflammatory factors, epoxidase-2, and angiotensinogen. 25,26 It is reported that Angiotensin II-induced mitochondrial dysfunction reduces endothelial NO bioavailability and promotes ROS generation, 27 therefore Angiotensin II-impaired mitochondrial function could be one of the mechanisms of endothelial dysfunction. Besides, the renin-angiotensin system (RAS) can be activated by angiotensin II to inhibit the function of progenitor cells, which has been reported to be beneficial to the recovery of VEC function and alleviates the symptoms of arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Notch/NF-κB signaling pathway is highly related to the process of angiogenesis (36)(37)(38)(39)(40). Notch1 is part of the Notch family that regulates cell fate and VEGF expression in various types of cell, including HUVEC (10,39,41).…”
Section: Discussionmentioning
confidence: 99%
“…We also co‐transfected 100 ng of either pMIR‐ cryab or pMIR‐ hspb2 together with si‐TBX5 or si‐NC as well as 20 ng of the pRL‐TK vector containing the renilla luciferase gene. Forty‐eight hours after transfection, cells were harvested, and used for luciferase assays using the Dual Luciferase Reporter Assay System (Promega) as described by us previously 35 . Luciferase activities were normalized to Renilla luciferase activity.…”
Section: Methodsmentioning
confidence: 99%